(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
This article focuses on the situation of the digital economy, which has become an integral part of the modern lifestyle, related to educational processes, and the author formulates a narrow and broad interpretation of the digital economy in the article, and comments on the differences between them. It is brought as a result of connection to the field of education and training. The main directions of introducing information technologies into the educational system are indicated separately, the pedagogical goals of using information and computer technologies in the educational process are considered.